Short-run underpricing of the Chinese Initial Public Offerings (IPO) in the Singapore market. - Chong, Chee Siang. (2008)
This study investigates the possible explanations behind the financial anomaly that is initial public offerings (IPO) underpricing, in the Singapore context, using data on 94 Chinese IPOs listed on the SGX Mainboard from the period 17th August 1981 to 31st December 2006.